2011
DOI: 10.1007/s00122-011-1713-6
|View full text |Cite
|
Sign up to set email alerts
|

Response to imazapyr and dominance relationships of two imidazolinone-tolerant alleles at the Ahasl1 locus of sunflower

Abstract: Imisun and CLPlus are two imidazolinone (IMI) tolerance traits in sunflower (Helianthus annuus L.) determined by the expression of different alleles at the same locus, Ahasl1-1 and Ahasl1-3, respectively. This paper reports the level of tolerance expressed by plants containing both alleles in a homozygous, heterozygous and in a heterozygous stacked state to increasing doses of IMI at the enzyme and whole plant levels. Six genotypes of the Ahasl1 gene were compared with each other in three different genetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
5
16
0
Order By: Relevance
“…Because of the high sensitivity of meristematic tissues, one of the first visible effects of AHAS-inhibitors is growth inhibition (Shaner and Mallipudi, 1991). The chlorosis and partial deformation of younger leaves that we observed in imazamox-treated sunflower plants correspond with what other authors reported (Sala et al, 2012). The appearance of chlorosis in the leaves of imazamox-treated sunflower plants in our study was due to their significantly lower chlorophyll content (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because of the high sensitivity of meristematic tissues, one of the first visible effects of AHAS-inhibitors is growth inhibition (Shaner and Mallipudi, 1991). The chlorosis and partial deformation of younger leaves that we observed in imazamox-treated sunflower plants correspond with what other authors reported (Sala et al, 2012). The appearance of chlorosis in the leaves of imazamox-treated sunflower plants in our study was due to their significantly lower chlorophyll content (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…AHAS-inhibiting herbicides are a broad group, which is widely used due to their high weed control efficacy, high crop-weed selectivity, low application rates, low levels of mammalian toxicity as well as their favorable environmental profile (Shaner and Singh, 1997). However, following imazamox application, temporary yellowing and growth retardation can occur, even in IMI-R sunflower hybrids (Hanson et al, 2006; Sala et al, 2012). These effects are transient and can be more pronounced when crops are growing under stressful environmental conditions (heat, drought, waterlogged soils, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [15] reported IMI resistance as a dominant trait based on the analysis of ALS activity in F 1 CL/WR hybrids. On the contrary, Tan et al [33] and Sala et al [34] characterize this trait as semi-dominant. Likewise, Bond and Walker [35] found that hybrid CL cultivars were less tolerant to IMI than the homozygous variety CL161, and results from IMI dose-response studies in ALS extracted from homozygous and heterozygous CL cultivars also support semidominant IMI resistance.…”
Section: Approach Iii: Agreement Between As-pcr and Kaspmentioning
confidence: 96%
“…Lines and hybrids carrying the CLPlus mutation have better tolerance to IMI herbi-cides and commercial tolerance levels can be achieved incorporating CLPlus in only one parent of a Clearfield hybrid, thus allowing more rapid development of the hybrid. The allele Ahasl1-3 has been found to be dominant over Ahasl1-1 (Sala et al, 2012). New sources of resistance to IMI herbicides have been recently identified in populations of wild H. annuus and H. argophylus (Christov et al, 2010).…”
Section: Use Of Herbicide-tolerant Cultivarsmentioning
confidence: 99%